Clinical Relevance and Tumor Growth Suppression of Mitochondrial ROS Regulators along NADH:Ubiquinone Oxidoreductase Subunit B3 in Thyroid Cancer. (17th January 2022) - Zhu, Jiao; Zheng, Xiaobo; Lu, Dan; Zheng, Yun; Liu, Jun
Abstract : Mitochondrial reactive oxygen species (mitoROS) are a double-edged sword in cancer progression, connoting the ROS-dependent malignant transformation and the oxidative stress-induced cell death. However, the underlying role of mitoROS in thyroid cancer remains unclear. Here, we collected 35 prominent mitoROS regulators to stratify 510 thyroid cancer patients in TCGA cohort through consensus clustering. Three molecular subtypes (cluster 1/2/3) were identified, among which cluster 1 (mitoROS low ) was preferentially associated with unfavorable prognosis. Individually, there were 12 regulators with a high expression that predicted a significantly favorable progression-free survival. The NADH:Ubiquinone Oxidoreductase Subunit B3 (NDUFB3) had a highest impact. NDUFB3 knockdown significantly reduced mitoROS levels in BCPAP and C643 cells. Bioinformatically, the consistency between NDUFB3 expression and cluster 1/2/3 was confirmed; lower expression of NUDFB3 was associated with a poor clinical outcome. Pathway analysis of differentially expressed genes in the NDUFB3 low and NDUFB3 high cohorts revealed a predominance of oxidative phosphorylation pathway changes. Consistently, mitochondrial functions, including oxygen consumption rate, ATP levels, complex I activity, mitoROS levels, and the expression of mitochondrially encoded NADH:Ubiquinone oxidoreductase core subunit 5, were significantly increased in NDUFB3-overexpressed BCPAP cells or C643 cells. The in vivo NDUFB3 overexpression and sideroxylin treatment significantly suppressed tumor growth and prolonged survival, concurrently elevating mitoROS levels ex vivo in mouse xenograft models. Conversely, NDUFB3 knockdown had the opposite effect. Together, these findings implicated the importance of mitoROS regulators in predicting clinical outcomes of patients with thyroid cancer. Our findings may pave the way for developing a mitoROS-based treatment for thyroid cancer patients.